Response of Groundnut Varieties to Phosphorus Management in Groundnut-Baby Corn Cropping Sequence - Moinuddin, G.; Saren, B. K. (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted during 2019 and 2020 (March to August) at Regional Research Station, Bidhan Chandra Krishi Viswavidyalaya, Jhargram, West Bengal, India to find out the response of phosphorus management on growth and yield of groundnut varieties and its residual effect on succeeding baby corn. The three main plot treatments (variety- TAG 24, TG 51, TG 37A) and six subplot treatments of phosphorus dose were laid out in split plot design with three replications. Highest plant height (70.3 cm), number of branches plant-1 (8.5), crop growth rate (3.67 g m-2 day-1), pod yield (2007 kg ha-1), haulm yield (2876.22 kg ha-1), kernel yield (1360.76 kg ha-1) and oil yield (689.36 kg ha-1) were obtained with groundnut variety TG 51. Whereas phosphorus dose (100% RDF+PSB @ 25 g kg-1 of seed+FYM @ 2 t ha-1) provided highest value for the above characters. Interaction effect was significant for pod yield and kernel yield. The residual effect on succeeding baby corn was found maximum for variety TAG 24 and treatment (100% RDF+PSB @ 25 g kg-1 of seed+FYM @ 2 t ha-1) applied to previous groundnut. So, application of phosphorus @ 60 kg ha-1 along with P.S.B @ 25 g kg-1 of seed and F.Y.M @ 2 t ha-1 may be successful for groundnut variety TG 51 alone and TAG 24 in sequence with baby corn.